Penerapan Hadis Tematik tentang Berpakaian Islami dalam Budaya Fashion Muslim Modern - Siti Yulinda Nurhalimah; Muhammad Alif; Repa Hudan Lisalam (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
The development of modern Muslim fashion has significantly transformed the way Muslims express their identity, especially in Indonesia, the country with the largest Muslim population. However, the growing popularity of “modest wear” fashion does not always align with Islamic principles as taught in the Hadiths. This study aims to explore the Islamic dress code based on thematic Hadith analysis (maudhū’ī), identify core dressing principles in Islam, and evaluate their implementation within the modern Muslim fashion culture. This research applies a qualitative method through library research, employing the thematic approach to collect and analyze Prophetic traditions related to clothing. The findings reveal that Islamic principles of dress include covering the ‘awrah (private parts), avoiding excessive adornment (tabarruj), refraining from imitating the opposite gender or non-Muslim cultures, and upholding modesty and dignity. These hadiths offer ethical guidance that is not only normative but also practical in the modern socio-cultural context. The study concludes that modern Muslim fashion can serve as an effective medium for visual da'wah if it remains aligned with Hadith-based values. The synergy between religious principles and creative design can form a relevant and dignified Islamic lifestyle rooted in the teachings of the Prophet Muhammad saw.